La voce afona del padrone: Fenomenologia delle figure dominanti nella narrativa breve italiana del XXI secolo (Ticontre. Teoria Testo Traduzione, 2021)
The article focuses on two collections edited by Ediesse, the publishing organ of the CGIL:Laboriosi oroscopi (2006) and Il lavoro e i giorni (2008). It analyzes the literary representation of socially "dominant" figures in professional relationships. Five figures were found and studied: the "weak master", told within a relationship based on care; the university "baron", whose symbolic power acts inside and outside the university; the "paternalistic master", inserted in the industrial context and who reproduces a model that only appears to be past; the "foolish master", considered as an idiot; the "archetypal master", an immaterial figure who, however, has an influence on the actions of subordinate characters.